Integration of In Situ Simulation Into an Emergency Department Code Orange Exercise in a Tertiary Care Trauma Referral Center. Issue 2 (17th June 2020) - Carmichael, Harrison; Mastoras, George; Nolan, Caroline; Tan, Hung; Tochkin, Jeffrey; Poulin, Cari; Willmore, Andrew; Posner, Glenn
Abstract: Objectives: Disaster‐preparedness and response are a commonly overlooked aspect of hospital policy and can frequently be outdated and undertested. Simulation‐based education has become a core education modality within Canadian medical training programs. We hypothesized that integrating in situ simulation (ISS) into a hospital‐wide, mass‐casualty response exercise would enhance realism and our ability to identify latent safety threats (LSTs). Methods: Using ISS we created a simulated mass shooting scenario with 20 patients, played by actors in full moulage, presenting to a large tertiary care hospital over a 50‐minute period. Results: Integrating ISS into our exercise created a realistic experience for the participants involved and improved participant education, while imparting enough systemic stress to expose LSTs associated within patient care and hospital policy. Conclusion: Overall, ISS was successfully used and enhanced a large‐scale test of our hospital's mass‐casualty response plan.